Search for the Xb and other hidden-beauty states in the π+π-ϒ{hooked}(1S) channel at ATLAS - Onofre, A. (2015)
This Letter presents a search for a hidden-beauty counterpart of the X(3872) in the mass ranges 10.05--10.31 GeV and 10.40--11.00 GeV, in the channel Xb→π+π−Υ(1S)(→μ+μ−), using 16.2 fb−1 of s√=8 TeV pp collision data collected by the ATLAS detector at the LHC. No evidence for new narrow states is found, and upper limits are set on the product of the Xb cross section and branching fraction, relative to those of the Υ(2S), at the 95% confidence level using the CLS approach. These limits range from 0.8% to 4.0%, depending on mass. For masses above 10.1 GeV, the expected upper limits from this analysis are the most restrictive to date. Searches for production of the Υ(13DJ), Υ(10860), and Υ(11020) states also reveal no significant signals.